An Insight into the Suitability of Clayey Raw Materials: The Ceramic Provinces of the Northern Peloponnese and South Epirus, Greece - Vayia Xanthopoulou; Ioannis Iliopoulos (Buildings, 2023)
Corinth, Achaea in the northern Peloponnese, and Nicopolis in Epirus (Greece) have a strong archaeological record of ceramic production, from the Early Helladic to Late Roman periods. Important archaeological sites, such as Helike, Aigeira, the settlement of Derveni, and the cities of Patras and Nicopolis, offer data and findings of exceptional quality. One of the main pillars for the development of the ceramic production in these areas was the availability of local natural resources, among which are the clayey sedimentary deposits that outcrop in the area. This study investigates the physical-technological properties (plasticity and granulometry), the mineralogical composition of clayey raw materials, in order to test their suitability for ceramic production across the entire geographic area. Our aim was to differentiate the three main “ceramic” provinces, based upon the above-mentioned properties. New data from western Achaea and south Epirus are presented and compared with previous research conducted in Corinthia and eastern Achaea. The results obtained showed that the clays sampled from Corinthia and eastern Achaea are carbonatic materials of poor plasticity, whereas those from western Achaea and Epirus are either Ca-rich or Ca-poor materials, with the majority exhibiting a better plasticity. The results from this study are expected to constitute an important archaeometric tool for tackling archaeological issues by means of provenance and ceramic technology within the region and in the surrounding areas.